Pemikiran Dan Pengaruh Syeh Nawawi Al-Bantani Dalam Perkembangan Islam Di Nusantara - Fadhlulloh, A Usis (Tanjak: Sejarah dan Peradaban Islam, 2024)
This article discusses the influence and contribution of Syeikh Nawawi al-Bantani to the spread of Islam in the archipelago. One of the leading scholars from Banten in the 19th century, Syeikh Nawawi al-Bantani, made a significant contribution to the spread of Islam in this region. Sensitivity and tolerance became a strong foundation for inter-ethnic and religious harmony in the Nusantara society, which was realized in a wise approach in understanding religious differences. The influence of Syeikh Nawawi al-Bantani covers social and educational aspects as well as limited to religious aspects. This article explains the role of madrasas and pesantren as centers of knowledge dissemination in the archipelago. His contribution to Islamic education helped develop the intellectual capacity of the local community and gave birth to a new generation of Islamic scholars who uphold the teachings of Islam. In addition, the article highlights recurring themes in the contemporary context of Syeikh Nawawi al-Bantani's writings. Ignorance of the past is an obstacle to racial tolerance in the archipelago today. Through intellectual reflection, this article offers insights into how the writings of Syeikh Nawawi al-Bantani continue to play an important role in shaping Islamic identity in the archipelago.